ASSESSMENT OF THE INFLUENCE OF STRUCTURAL DAMAGE ON THE AIRCRAFT CHARACTERISTICS OF THE AIRCRAFT - Ліпіхін, С. В. (Proceedings of National Aviation University (archive), 2021)
The influence of structural damage on the aerodynamic characteristics of the aircraft, the dependence of the main aerodynamic characteristics on mechanical damage is analyzed. The most dangerous and least predictable events that lead to structural damage are considered. A probable estimate of the occurrence of structural damage on the aircraft is given. The reflection of the changed aerodynamic parameters through the creation of systems of flight control parameters of the aircraft is offered.